2014
DOI: 10.1097/mao.0000000000000185
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral Cochlear Implantation After Cochlear Nerve Preserving Vestibular Schwannoma Surgery in Patients With Neurofibromatosis Type 2

Abstract: The present series demonstrates that in selected cases, cochlear implantation can be successful after a translabyrinthine approach for VS removal and for restoring hearing after failed retrosigmoid hearing preservation surgery. All patients found the cochlear implant offered useful hearing even in the presence of contralateral hearing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 30 publications
2
45
0
Order By: Relevance
“…Cochlear implantation has been previously described for the hearing rehabilitation of patients with NF-2 and sporadic VS in the only or better hearing ear [Lustig et al, 2006;Odat et al, 2011;Carlson et al, 2012;Di Lella et al, 2013;Lloyd et al, 2014;Aristegui and Denia, 2015;Lassaletta et al, 2016]. However, little is known about their benefits in the presence of normal contralateral hearing after VS resection.…”
Section: Discussionmentioning
confidence: 99%
“…Cochlear implantation has been previously described for the hearing rehabilitation of patients with NF-2 and sporadic VS in the only or better hearing ear [Lustig et al, 2006;Odat et al, 2011;Carlson et al, 2012;Di Lella et al, 2013;Lloyd et al, 2014;Aristegui and Denia, 2015;Lassaletta et al, 2016]. However, little is known about their benefits in the presence of normal contralateral hearing after VS resection.…”
Section: Discussionmentioning
confidence: 99%
“…Lloyd et al [33] have recently published results of this type of approach using either retrosigmoid or translabyrinthine surgery and have demonstrated that it is possible to gain significant benefit from a cochlear implant in the majority of patients. It seems that cochlear implantation alone in patients with profound hearing loss and stable tumours is a further option and has been shown to produce effective hearing rehabilitation with post implantation speech discrimination scores of around 60 % [34,35].…”
Section: Discussionmentioning
confidence: 97%
“…Most ABI users gained enhanced communication skills when combined with LR to an extent that was greater than the sum of the two individual skills. Subjectively these abilities are of value (7,8). In only a very small number of individuals was performance with the ABI comparable to that expected from a cochlear implant, most of whom achieve open-set speech understanding and high sentence scores even in NF2 (9).…”
Section: Discussionmentioning
confidence: 99%